Unveiling The “Five Catalysts” For The Success Of The Core Tax Project - Juwita, Syerlin; Qadri, Resi Ariyasa (Educoretax, 2024)
The objective of this investigation is to evaluate the determinants impacting the efficacy of the Volume III tax reform, specifically the implementation of the Core Tax Administration System, among employees as primary users of these system enhancements. Employing a qualitative case study methodology, this research scrutinizes the experiences of staff at the Small Tax Office of Muara Bungo. Utilizing both primary data, derived from questionnaires and interviews, and secondary data, sourced from an extensive literature review, this study employs thematic analysis to dissect the data. The findings identify five critical factors influencing the successful implementation of the Core Tax Administration System Update. These insights aim to inform the Directorate General of Taxes about critical considerations necessary for augmenting preparedness and optimizing the execution of tax reform initiatives.